Controls on the cadmium isotope composition of modern marine sediments - Bryan, AL; Dickson, AJ; Dowdall, F; Homoky, WB; Porcelli, D; Henderson, GM (Elsevier, 2021)
Continental margin sediments have been identified as the dominant sink in the marine budget of cadmium (Cd). The isotopic composition of this important output flux is, however, unknown. Here we present, with measurements on the Argentine continental margin, the first observational constraints on the isotopic composition of Cd in modern marine oxic and sub-oxic sediments. We identify two main removal mechanisms of Cd; in organic material, and by sulfide formation. Surface margin sediments (0–0.5 cm), with dissolved O2 below detection from ∼0.5 cm, are isotopically lighter than overlying oxygenated waters. A mass balance for these surface sediments indicates that Cd is present dominantly as organically-bound particulate Cd. In sub-surface sediments, Cd concentrations increase in the zone of nitrate reduction, and attain similar isotopic compositions as the water that overlies the sediment (i.e. ∼0.35‰ in deep waters). These observations are consistent with a downward diffusive flux of seawater Cd and redox-driven quantitative removal of that Cd during sulfide precipitation. In combination, these two routes of Cd removal lead to burial of isotopically light organic Cd in margin sub-oxic sediments that enables the global isotopic Cd budget to be balanced.